Prevalence, MRI findings, and clinical features of lumbosacral intervertebral disc protrusion in French Bulldogs diagnosed with acute thoracic or lumbar intervertebral disc extrusion - La Rosa, Claudia; Morabito, Simona; Carloni, Andrea; Davini, Tommaso; Remelli, Carlotta; Specchi, Swan; Bernardini, Marco (Frontiers in Veterinary Science, 2023)
Introduction: Intervertebral disc protrusion (IVDP) is a neurological disorder commonly observed at the lumbosacral junction of old, medium-to-large breeds, non-chondrodystrophic dogs. Although uncommon, lumbosacral IVDP can also be seen in chondrodystrophic dogs, among them French Bulldogs (FBs) and could be associated with congenital vertebral malformations in this breed. This study aims to evaluate the prevalence, clinical features, and MRI characteristics of lumbosacral IVDP and congenital vertebral malformations in FBs diagnosed with thoracic or lumbar intervertebral disc extrusion (IVDE) and to evaluate the possible interference of the neurologic deficits related to chronic IVDP on neurological examination.This is a single-center, retrospective case series. A search for FBs diagnosed with IVDE affecting the thoracic or lumbar regions is done on the database of the AniCura I Portoni Rossi Veterinary Hospital (Zola Predosa, Bologna, Italy). Eligible dogs have a complete medical report and a high-field MRI of the lumbosacral junction. MRIs of the lumbosacral junction are evaluated to determine the position of IVDP, cranial intervertebral foraminal stenosis, and signs of nerve root involvement. Radiographs, when available, are reviewed to identify the presence of lumbosacral congenital vertebral malformations.Results: Eighty FBs are included in the study. The prevalence of lumbosacral IVDP among FBs is 91.3%. Among FBs with lumbosacral IVDP, 45.0% show concurrent cranial intervertebral foraminal stenosis, 28.8% exhibit concurrent nerve root involvement, 56.2% appear to be asymptomatic for lumbosacral changes, while 15.1% manifest a decreased or absent withdrawal reflex as a supposed consequence of chronic lumbosacral IVDP. Congenital vertebral malformations are detected in 10 dogs.The results of this study support the hypothesis that lumbosacral IVDP is frequent in FBs presenting with thoracic or lumbar IVDE. In over half the dogs lumbosacral IVDP appears to be asymptomatic; however, in other cases, chronic lumbosacral IVDP seems to cause neurological deficits that may lead to erroneous localization of acute IVDE, representing a confounding factor for clinicians.